ANALISIS KEMAMPUAN KERJA, COACHING DAN KINERJA KARYAWAN: STUDI KASUS PADA KARYAWAN PT SARI ATER HOTEL DAN RESORT SUBANG - Fauziatunisa, Hanani; Nuryanti, B Lena; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2018)
Purpose â€“ This study aims to determine the effect of work ability and coaching on employee performance at PT. Sari Ater Hotel and Resort Subang. Design/methodology/approach - This research uses descriptive approach with explanatory survey method. The employee analysis unit is 62Â  people from employees who have experienced coaching . Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings - The result showed that work ability is in good enough category, coachng is in effectif category. and performance in the high category Originality / value - The differences in this study located on an object research, time research, a measuring instrument , literature that used , the theory that is used and the results of the study